Open-Label-Placebos can reduce pain, but not indigestion during gluten challenge in chronic pain patients - Paschke-Dahl, Lena; Klinger, Regine (Frontiers in Psychology, 2025)
BackgroundDietary interventions have become a management tool for chronic pain conditions over the past few decades. Certain diets, such as gluten-free diets, are perceived as particularly beneficial by patients, although there is no evidence to support this. Studies that have investigated this topic have focused little on possible expectation effects that could be involved in symptom development or pain increase.MethodsIn a 2×2 study design with repeated measurements to test treatment effects, we investigated 26 patients with fibromyalgia (FMS). Additional chronic pain conditions were included and analyzed exploratively. However, the main analysis focused on fibromyalgia patients. Participants underwent an oral food challenge (OFC) with double-blinded gluten or alleged gluten (sham gluten). All of them received an OLP with different instructions to treat negative effects of the porridge. Treatment expectations were modulated by either neutral or positive instructions regarding the OLPs. Participants were randomly assigned to one of four groups: (1) gluten and neutral instructions; (2) gluten and positive instructions; (3) sham gluten and neutral instructions; and (4) sham gluten and positive instructions. Expectations before (T0) and after the instructions (T0.1) as well as pain and indigestion before (T0) and after the OFC (T1 30min, T2 30-180min, T3 240min) were assessed.ResultsIn FMS patients, a significant interaction with instructions were observed (p = 0.048). Positive instructions led to a decrease in pain (T0-T2) while neutral instructions led to an increase in pain. However, post-hoc comparisons did not reveal significant group differences. No interaction was found with gluten (p = 0.65). Positive instructions increased positive treatment expectations but missed significance marginally (p = 0.06), while negative expectations decreased for all participants regardless of instructions (p < 0.001). A strong correlation was found between expected and actual pain relief (p < 0.001). Digestive discomfort increased temporarily post-intervention (p < 0.004) but returned to baseline after 4 h. No significant effects of gluten (p = 0.15) or instructions (p = 0.8) on indigestion were observed.ConclusionThis study highlights the complex interplay of disease type, placebo effects, and expectations in chronic pain conditions during gluten provocation. While gluten itself showed no significant impact on pain or indigestion, positive instructions significantly enhanced perceived pain relief. These findings suggest that expectation effects, rather than gluten, may play a more central role in symptom modulation, at least for pain. Future research should focus on expectation-driven mechanisms to better understand and optimize dietary interventions in chronic pain management and differences across pain diseases.